AWOT (AHP–SWOT) Method for Determining Sustainable Food Agricultural Land Policy Strategies in Merauke Regency - Prihadi Beni Waluyo; Arum Ambarsari; Ineke Nursih Widyantari; Gerzon Jokomen Maulany (Journal of Global Sustainable Agriculture, 2026)
Population growth, coupled with a fixed land supply, has accelerated the conversion of agricultural land and may undermine food security. To address this issue, sustainable food agricultural areas need to be designated through the formulation of Sustainable Food Agricultural Land (LP2B) protection policy strategies to ensure that existing agricultural land can be preserved. This study aimed to analyse internal and external factors and formulate priority policy strategies for LP2B protection to control agricultural land conversion in Merauke Regency. The study was conducted in Merauke Regency, Papua Province, Indonesia (currently South Papua Province), from August to October 2020. The study site was purposively selected. Both primary and secondary data were used. Primary data were collected through questionnaires and interviews involving ten respondents, while secondary data were obtained from the Department of Agriculture and relevant literature. The analysis employed the AWOT approach, which integrates the Analytical Hierarchy Process (AHP) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The results identified eleven policy strategies for protecting sustainable food agricultural land in Merauke Regency. The highest-priority strategy was the designation of permanent food agricultural areas that should be strictly protected from conversion to non-agricultural uses.